Pelayanan Khotbah Melalui Radio-Radio Kristen Di Semarang - Sugiarto, Dewi Lisiani Kurniawan (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2020)
For some time, researchers have observed that the delivery of Christian radio sermons in Semarang was not as expected. For example, about sermons that are tedious, irrelevant, unclear, monotonous, unappealing, lacking in-depth discussion about less practical applications, and so on. Based on the background of the problem, the purpose of this study is to find out how to evaluate the preparation and after the delivery of sermons on Christian radios in Semarang. To get detailed data, researchers conducted a literature study and tested the statement with Expert Validation (in this case, the one who did it was a Supervising Lecturer), then the researcher then conducted an interview. The research method used is a qualitative method and descriptive. The number of participants in this study consisted of 72 preachers as both fillers and listeners of the program Christian radio stations in Semarang, and 5 Christian radio administrators in Semarang as data completeness. The overall results of the study indicate that the evaluation of the preparation and after the delivery of sermons on Christian radios in Semarang is well categorized. By relying on the Holy Spirit, the network / signal is not interrupted, the receiver and transmitter are good, the preparation and weight of the sermon material, the composition of the sermon in Explanation, Illustration and proportional application, according to the needs of the listener, applicative, and the delivery method are lived, varied, clear, interesting. Thus, the ministry of radio preaching will be able to reach more and more souls and the name of the Lord Jesus Christ is increasingly glorified!Beberapa lama ini peneliti mengamati bahwa pelaksanaan pelayanan khotbah radio-radio Kristen di Semarang kurang sebagaimana diharapkan. Misal, tentang khotbah yang menjemukan, tidak relevan, tidak jelas, monoton, tidak menarik, pembahasan kurang mendalam penerapan yang kurang mengena, dan lain-lain.Berdasar latar belakang masalah tersebut, maka tujuan penelitian ini untuk mengetahui bagaimana evaluasi persiapan dan setelah penyampaian khotbah di radio-radio Kristen di Semarang. Untuk mendapat data secara rinci, peneliti melakukan Studi Pustaka dan menguji pernyataan dengan Validasi Ahli (dalam  hal ini, yang melakukannya adalah Dosen Pembimbing), baru kemudian peneliti melakukan wawancara Metode penelitian yang digunakan adalah metode kualitatif dan deskriptif. Jumlah partisipan penelitian ini terdiri dari 72 orang pengkhotbah sebagai pengisi sekaligus pendengar acara khotbah radio-radio Kristen di Semarang, dan 5 orang pengurus radio-radio Kristen di Semarang sebagai kelengkapan data.Hasil penelitian secara keseluruhan menunjukkan bahwa evaluasi persiapan maupun setelah penyampaian khotbah di radio-radio Kristen di Semarang dikategorikan baik. Dengan bergantung pada Roh Kudus, jaringan/sinyal tidak terganggu, receiver dan transmitter baik, persiapan dan materi khotbah berbobot, komposisi khotbah dalam Penjelasan, Ilustrasi dan aplikasi proporsional, sesuai kebutuhan pendengar, aplikatif, dan cara penyampaian dihidupi, bervariasi, jelas, menarik. Dengan demikian, pelayanan khotbah radio akan dapat semakin banyak menjangkau jiwa-jiwa dan nama Tuhan Yesus Kristus semakin dimuliakan!